2018
DOI: 10.3389/fpubh.2018.00201
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Pattern, Hypertension and Cognitive Function in an Older Population: 10-Year Longitudinal Survey

Abstract: Background: There is a paucity of studies that have explored the association between dietary pattern and cognitive function, and whether there is an interaction between dietary pattern and hypertension in relation to older people's cognitive functioning.Methods: We analyzed data from the China Health and Nutrition (CHNS) survey. Dietary data have been collected since 1991, and cognitive function interview data were collected between 1997 and 2006. We analyzed ten years of data, including 4,847 participants wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 49 publications
1
18
0
1
Order By: Relevance
“…In a Taiwanese study on older adults, the “traditional dietary pattern” (characterized by a high pickled vegetable intake) protected against the decline in logical memory recall [ 33 ]. By contrast, in a Chinese longitudinal study involving 4847 participants aged 55 years or older, it was approved that the “starch-rich dietary pattern”, in particular salted vegetables and legumes, was positively associated with cognitive decline [ 34 ]. In the current study, high pickled vegetable intake was positively associated with cognitive impairment and frailty.…”
Section: Discussionmentioning
confidence: 99%
“…In a Taiwanese study on older adults, the “traditional dietary pattern” (characterized by a high pickled vegetable intake) protected against the decline in logical memory recall [ 33 ]. By contrast, in a Chinese longitudinal study involving 4847 participants aged 55 years or older, it was approved that the “starch-rich dietary pattern”, in particular salted vegetables and legumes, was positively associated with cognitive decline [ 34 ]. In the current study, high pickled vegetable intake was positively associated with cognitive impairment and frailty.…”
Section: Discussionmentioning
confidence: 99%
“…27 Thus, malnutrition signifies a lower level of serum albumin. Xu et al 28 deemed that a protein-rich dietary pattern was significantly associated with higher cognitive global scores and verbal memory scores. We obtained similar findings in our study; patients with COPD at risk of malnutrition had a lower level of albumin, and albumin was positively correlated with cognitive function ( Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…For example, our findings are consistent with another study using CHNS data. Xu et al found that protein-rich dietary pattern (high intake of milk, eggs and soymilk) was positively but a starch-rich dietary pattern (high intake of salted vegetable, whole grain and legumes) was inversely associated with global cognition in CHNS [48].…”
Section: Discussionmentioning
confidence: 99%